Total Quality Management: Perspective of Saudi Healthcare Organizations (Journal of Business Management and Accounting, 2019)
Total Quality Management is essential in the healthcare sector. Delivering good healthcare services is one of the main issues among healthcare organizations. Healthcare customers are satisfied with healthcare providers when their services meet the level of their expectations. Satisfying healthcare customers (both public and private) can be attained through Total Quality Management. This paper highlights the importance of using Total Quality Management in healthcare organizations in the Kingdom of Saudi Arabia (KSA). A review of the implementation of TQM among Saudi healthcare organizations highlighted the challenges faced in the sector. The sustained efforts in improving the service quality in Saudi healthcare have led to remarkable results. However, there are more challenges regarding the quality of services. This paper is helpful for strategic planners, policy makers, and management in the KSA healthcare sector and in other jurisdictions.